ARSITEKTUR KAMPUNG BAGI PEMULIHAN KEHIDUPAN SOSIAL-EKONOMI KAMPUNG KERANG MELALUI INTERVENSI WISATA BLUSUKAN DAN INDUSTRI MIKRO - Sera Joanne Abigail; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Cilincing Coastal Area in the past served as one of the centers of tourism and trade, as well as a fishing port in Jakarta. Since the growth of the industrial area, the socio-economic conditions of the people on the Cilincing coast have experienced degradation, which is marked by high poverty rates, the emergence of slum settlements, and low education. This phenomenon also occurred in Kampung Kerang, a fisherman village in Kalibaru, Cilincing, North Jakarta. The existence of industrial areas causes a fluctuating flow of urbanization and urges the activities of fishermen who are still left in this area. This study aims to design an architectural project for socio-economic improvement in Kampung Kerang, especially fishermen who still depend on marine products. Through the Urban Acupuncture concept, 'Bale Kijing' Architecture seeks to embrace local wealth in the form of traditional salted fish and mussel processing industries, as well as ‘blusukan’ tourism as a potential for regional economic recovery. This research is using descriptive qualitative method through the study of literature studies from various sources. Architectural processes are bridged by ‘everydayness’ methods. Through observation and mapping of physical characters and daily activities in Kampung Kerang, data were obtained regarding the tendency of architectural characters and patterns of social interaction in Kampung Kerang, then translated into the architectural form of 'Bale Kijing'. Through this approach, it is hoped that a form of architectural intervention can be created that is close to everyday life, and involves the active participation of the community. Keywords:  ‘Blusukan’; ‘Kijing’; Salted-Fish; Urban Acupuncture; Village Abstrak Kawasan Pesisir Cilincing di masa lampau berperan sebagai salah satu pusat pariwisata dan perdagangan, serta pelabuhan ikan di Jakarta. Semenjak pertumbuhan kawasan industri, kondisi sosial-ekonomi masyarakat di pesisir Cilincing mengalami degradasi yang ditandai dengan tingginya angka kemiskinan, munculnya permukiman kumuh, dan rendahnya pendidikan. Fenomena tersebut juga terjadi di Kampung Kerang, salah satu kampung nelayan di Kalibaru, Cilincing, Jakarta Utara. Keberadaan area industri menyebabkan arus urbanisasi yang fluktuatif serta mendesak aktivitas nelayan yang masih tersisa di kawasan ini. Penelitian bertujuan untuk merancang proyek arsitektur bagi peningkatan sosial-ekonomi masyarakat miskin di Kampung Kerang, khususnya nelayan yang masih bergantung pada hasil laut. Melalui konsep Urban Acupuncture, Arsitektur ‘Bale Kijing’ berusaha merangkul kekayaan lokal berupa industri tradisional pengolahan ikan asin dan kijing, serta wisata blusukan kampung sebagai potensi pemulihan ekonomi kawasan. Penelitian ini menggunakan metode kualitatif deskriptif melalui pengkajian terhadap studi literatur dari berbagai sumber. Proses berarsitektur dijembatani oleh metode keseharian. Melalui observasi dan pemetaan terhadap karakter fisik dan aktivitas keseharian di Kampung Kerang, didapatkan data mengenai kecenderungan karakter arsitektur dan pola interaksi sosial di Kampung Kerang yang kemudian diterjemahkan ke dalam bentuk arsitektur ‘Bale Kijing’. Melalui pendekatan ini diharapkan dapat tercipta suatu bentuk intervensi arsitektur yang dekat dengan keseharian, serta melibatkan partisipasi aktif masyarakat.